Effects of cooling rate on the electrical properties of Pb-free BF-BT ceramics. (10th December 2019) - Khan, Salman Ali; Akram, Fazli; Malik, Rizwan Ahmed; Hussain, Ali; Kim, Jun Chan; Song, Tae Kwon; Kim, Won-Jeong; Sung, Yeon Soo; Kim, Myong-Ho; Lee, Soonil
Abstract: The ferroelectric, piezoelectric and dielectric properties of the air- and water-quenched samples of 0.65Bi1.05 Fe1- x Ga x O3 –0.35BaTiO3 ( x = 0 and 0.02) lead-free ceramics were investigated. X-ray diffraction patterns showed that the Ga modification and different cooling rates during sintering did not cause any significant change in the crystal structure. It is believed that the significant enhancement of ferroelectric and piezoelectric properties is attributed to the relaxation of the lattice strain induced in the samples, to better understand the quenching effects and thereby improvement in electrical properties, by modification and reduction of associated defects concentration with rapid cooling. For the optimum composition ( x = 0.02), an enhanced piezoelectric constant d 33 of 156 pC/N was observed from the water quenched sample.